Implementation of sustainable farming practices by cocoa farmers in Ecuador and Uganda: the influence of value chain factors - Tennhardt, Lina M.; Lambin, Eric F.; Curran, Michael; Schader, Christian (Frontiers in Sustainable Food Systems, 2023)
A key strategy of chocolate manufacturers is the promotion of sustainable farming practices among their supplying cocoa producers. A growing body of micro-economic literature has analysed factors influencing the adoption of such practices, yet broadly disregarded value chain factors. Information on how factors within single value chains increase the adoption of sustainable farming practices can help direct chocolate companies' investments and increase return of investments in sustainability. The objective of this study was to understand: a) how important value chain factors are, relative to farmer and farm factors, for cocoa farmers' implementation of sustainable farming practices and b) through which mechanisms value chain factors influence sustainable farming practices implementation. By integrating the practice adoption with sustainable supply chain management literature, we contribute to closing an important research gap. We collected data from 394 cocoa farmers in Ecuador and Uganda and analysed the determinants of implementation sustainable farming practices, testing quantitatively whether value chain factors with variation within single value chains are significantly associated with practice implementation. These factors included information factors (farmers' access to training; advisory service through the value chain) and structural factors (value chain organisation and persistence; farmers' dependency on this value chain). We selected 11 sustainable farming practices or indicators across three sustainability dimensions, i.e. environmental, social, and economic. We found that value chain factors are comparable to farmer and farm factors in explaining the implementation of sustainable farming practices across dimensions. Both capacity building and stable relationships were significantly related with the implementation of certain sustainable farming practices. Yet these results were weaker than expected, indicating that their potential was not fully exploited within our case study value chains. Through their value chain sustainability initiatives, chocolate companies should disseminate knowledge, address inhibitors to sustainable farming practices implementation beyond knowledge, and align sustainability goals with all value chain actors.